2018
DOI: 10.1155/2018/8098059
|View full text |Cite
|
Sign up to set email alerts
|

Gypenosides Altered Hepatic Bile Acids Homeostasis in Mice Treated with High Fat Diet

Abstract: Gypenosides extracted from Gynostemma pentaphyllum (Thunb.) Makino have significant role in reducing serum lipid level and treating fatty liver diseases, however, without clear mechanism. As gypenosides share the similar core structures with bile acids (the endogenous ligands of nuclear receptor FXR), we hypothesize that gypenosides may improve hypercholesterolemia via FXR-mediated bile acids signaling. The present study was designed to validate the role of gypenosides in reducing levels of serum total cholest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 39 publications
2
12
0
1
Order By: Relevance
“…Moreover, we observed that Gyp treatment could significantly reduce the TBA content as well as the aMCA, TaMCA, βMCA, TβMCA TCDCA, CA, GCDCA, GCA and TCA content and significantly increased the alloLCA and βCDCA content in liver tissues from NASH mice, and thus, it promoted hepatic bile acid homeostasis. In agreement, previous research demonstrated that Gyp can alter the liver bile acid homeostasis induced by a HFD [41]. Also, Gyp treatment successfully regulated the adipose thermogenesis and gut microbiota, which were reduced in the process of gaining weight [42].…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, we observed that Gyp treatment could significantly reduce the TBA content as well as the aMCA, TaMCA, βMCA, TβMCA TCDCA, CA, GCDCA, GCA and TCA content and significantly increased the alloLCA and βCDCA content in liver tissues from NASH mice, and thus, it promoted hepatic bile acid homeostasis. In agreement, previous research demonstrated that Gyp can alter the liver bile acid homeostasis induced by a HFD [41]. Also, Gyp treatment successfully regulated the adipose thermogenesis and gut microbiota, which were reduced in the process of gaining weight [42].…”
Section: Discussionsupporting
confidence: 90%
“…Our study shows that high fat diet mice were inhibited expression of Cyp8b1 and Cyp7a1. Cholesterol catabolism into bile acids was inhibited, which caused the cholesterol elevated cholesterol [39].…”
Section: Discussionmentioning
confidence: 99%
“…An increased concentration of the primary bile BAs CA and CDCA [44], with a consequent increase of their ratio, has been evaluated as a marker of intrahepatic cholestasis of pregnancy [45] and progressive familial intrahepatic cholestasis [46]. More recently, changes have been observed in animal models and patients affected by NAFLD and NASH [47,48]. Coherently, we also observed a significant increase of the CDCA drop of CA plasma concentration in rats fed with a Western diet, but there was a significant drop of CA, leading to a decrease of the CA:CDCA ratio.…”
Section: Discussionmentioning
confidence: 99%